THE INFLUENCE OF POLITICAL CONNECTIONS ON CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE IN INDONESIA - Kurnikova, Afia Ayu; Sucahyati, Diarany (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
This study aims to analyze the link between CSR disclosure and politically connected companies. A quantitative approach utilizing multiple linear regression analysis in Stata version 17 was used to analyze the association between independent and dependent variables in all corporations registered on the Indonesia Stock Exchange from 2019 to 2023, leaving out the financial and banking sectors, resulting in 1,105 companies. This study found that the availability of political connections encourages increased CSR disclosure to strengthen relationships with stakeholders and build a positive image in the eyes of the public for the benefit of the business. This study is interesting because it focuses on a single period of the latest government regime in Indonesia as a developing country, thus enabling more consistent results that are free from potential policy bias due to leadership changes.